KantowskiSachs Bulk Viscous String Cosmological Model In Gravity With Time Varying Deceleration Parameter (Global Journal of Science Frontier Research, 2018)
We propose a specially homogeneous and anisotropic Kantowski-Sachs string cosmological model with bulk viscosity in the framework of ( ) T R f , gravity by considering two cases (i) the special form and (ii) linearly varying deceleration parameter. To obtain a deterministic solution of the field equation we have been used some physical plausible condition. In this theory, cosmological model is presented in both cases. Also some important features of the models, thus obtained, have been discussed.
Keywords: f (R; T )gravity; bulk viscous fluid; cosmic string; deceleration parameter